Dividend access shares (stapled stock) : proceedings of a seminar held in Cannes, France in 1995 during the 49th Congress of the International Fiscal Association.: proceedings of a seminar held in Cannes, France in 1995 during the 49th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available